The Political Strategy of a Migrant Candidate in Pilkades of Batu Meranti Village (POLITEA, 2020)
In academic literature, the term political identity such as primordial is nothing new, Clifford Geertz, as an American anthropologist introduced that term in the 1960s. Indonesia as a multicultural nation with diverse identities also has a political identity’s problem even at the national or local level. This study has brings the opponent's argument which found that Primordial issues are not the determinant factor of people's choice in a political election, cause identity was fluid, have interchangeable nature, and related in many aspects. This research used a qualitative method with a study cased approach located in Batu Meranti Villages, in South Kalimantan. Key informants were all of the candidates, the winning team of candidates, KPU, BPD, and the community in Batu Meranti Village. The data collection techniques are carried out by field research techniques, library research techniques, and documentation method techniques. The result was shown that people's perspectives have transformed the identity issue to be habitus of all candidates. The migrant candidate political strategy to win the political scramble was used the harmonization of generated formula to use his personality, economic capital, and most people's concern about those village. The migrant candidates have used the opportunity to show his personality as philanthropist and concern with soccer to get a good image and get support from society. In the end, the personality of a candidate has been replaced by the identity issue in a local election.